Application of the lambda plate on condylar fractures: Finite element evaluation of the fixation rigidity for different fracture patterns and plate placements. Issue 4 (April 2022) - Liokatis, Paris; Tzortzinis, Georgios; Gerasimidis, Simos; Smolka, Wenko
Abstract: Purpose: The treatment challenges of condylar fractures necessitated the production of several plate designs. Among the relatively new plate designs is the lambda plate, for which biomechanical and clinical data are lacking. The purpose of this study is to examine the rigidity of fixation achieved when the lambda plate is applied to different fractures of the condylar neck and base. Methods: Five fractures of the condylar area were designed on a virtual model of a healthy mandible obtained from a CT scan. The fractures were reduced using the lambda plate. For the same fractures, alternative placements of the plate were simulated. The generated models were analysed using the finite element analysis for a 500 N bite load. The displacement of the two condylar fragments along the fracture line was calculated as an indicator of the rigidity of the fixation. Results: The displacement along the fracture was less than 0.144 mm for the neck fractures and greater than 0.165 mm for the fractures of the condylar base. A more cranial placement of the plate for the neck fractures further reduced the displacement, while a more anterior placement of the plate for the base fractures resulted in displacements greater than 0.330 mm. Conclusion: According to our study, the lambda plate offers better rigidity when applied as cranially as possible for condylar neck fractures. The lambda plate did not provide adequate fixation for base fractures. A second plate at the sigmoid notch should be considered to achieve better stabilization along the fracture if the lambda plate is eventually used.